Brunei Darussalam : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Brunei Darussalam. (IMF Staff Country Reports; Country Report ;, 2021)
Brunei's economic performance-which was strong before the COVID-19 pandemic-has been buffeted by the health crisis and a pandemic-induced oil and gas price shock. The authorities responded fast and decisively. The number of new infections was quickly suppressed, thanks to a swift public health response, effective health measures and non-pharmaceutical interventions. Strong fiscal and regulatory policy responses helped sustain production and household income and consumption. Past diversification efforts and reforms bore fruit when it was most needed. As a result, the economy performed strongly in 2020, with real GDP posting positive growth of 1.1 percent-a rare outcome amidst negative growth in the region. Economic activity is projected to strengthen in 2021-22, albeit at varying speeds across sectors, and to continue improving over the medium term on the back of further diversification. The outlook is, however, subject to unusual uncertainty, with significant risks skewed to the downside. Sustained strong policy actions are needed to ensure continued resilience, while nurturing green, digital and inclusive growth.